Networked learning assessment through blogs and rubrics: complements or supplements? - Antonio R. Bartolomé Pina; Esther Martínez-Figueira; Fernando Tellado-González (Universitat Politècnica de València, 2014)
This article is related to the use of blogs and rubrics as resources in networked learning assessment in order to value if these tools could serve as complement or supplement in the process. The sample was composed of 118 students who were reading and "Didactic and curriculum" (Pedagogy Degree) from the University of Barcelona; and "New Technology applied to Childhood Education" (Degree in Childhood Education) and "New Technology applied to Primary Education" (Degree in Primary Education), both from de University of Vigo. The methodology is part of I+D Project EDU2010-15432, than have allowed to study two groups of students: group 1 made up for that students who made their personal diary in blogs, as an element to increase the structure, synthesis, self-analysis and reflection about their learning; and group 2 made up for students who, also using blogs, used self-assessment rubrics as a complement or supplement about them. It expects to denote the rubrics influence has been both mastery of content and skills development, and involve students in the assessment process when blogs are used in it. The results show that the use of the rubrics as a complementary element to blogs, intensify the benefits fs those when working competences development.